Several Dynamical Properties for a Nonlinear Shallow Water Equation. (22nd May 2014) - Yong, Ls; Yan, Haibo
Abstract : A nonlinear third order dispersive shallow water equation including the Degasperis-Procesi model is investigated. The existence of weak solutions for the equation is proved in the space L 1 ( R ) ∩ B V ( R ) under certain assumptions. The Oleinik type estimate and L 2 N ( R ) (N is a natural number) estimate for the solution are obtained.